Visual Dysfunction In Recent Onset Diabetes: A Clinical Report - Lovasik, J.V; Kothe, A.C (Canadian Journal of Optometry, 2021)
A clinical report is presented of a 64 year old patient with recent onset diabetes. Simple in-office test procedures for the detection of subtle functional abnormalities in the visual system are presented. Diagnostic findings are expanded by results of electrophysiological testing, and complemented by an investigation of vascular structural integrity by fluorescein angiography. The importance of an examination routine consisting of an assessment of both functional and structural aspects of the visual elements typically affected by the diabetic condition is emphasized.